The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00508-006-0530-4
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant laser acupuncture in the treatment of whiplash injuries: a prospective, randomized placebo-controlled trial

Abstract: Adjuvant laser acupuncture with a 5 mW HeNe laser and an irradiation time of 15 s appears to be ineffective in the management of whiplash injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…These findings are of direct relevance to the clinical application of LLLT showing its effectiveness in painful conditions such as neck or back pain. Clinically, LI is applied transcutaneously to multiple points, such as tender points, 78 trigger points, 79 or acupuncture points, 80 in the region of injury or pathology. The neural network of nociceptor fibers within the epidermis would be most affected by the transmitted photons, as photon density is maximal in the epidermis and decreases exponentially.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are of direct relevance to the clinical application of LLLT showing its effectiveness in painful conditions such as neck or back pain. Clinically, LI is applied transcutaneously to multiple points, such as tender points, 78 trigger points, 79 or acupuncture points, 80 in the region of injury or pathology. The neural network of nociceptor fibers within the epidermis would be most affected by the transmitted photons, as photon density is maximal in the epidermis and decreases exponentially.…”
Section: Discussionmentioning
confidence: 99%
“…41 Therefore, only six acupuncture studies for acute neck pain/whiplash were reviewed. Harmful adverse events were rarely reported, and four studies testing electroauricular acupuncture, 42 laser acupuncture, 43 and distant acupuncture 44,45 reported a significant effect compared to SA, while in the other studies, the results of laser, 46 dry needling, 44 and auricular acupuncture 47 were reported to be negative. After weighing the benefits and risks, a rating between B and C was suggested.…”
Section: Acupuncture For Selected Neurologic Disorders: An Overview Omentioning
confidence: 99%
“…Studies performed by Carvalho et al, 21 Gur et al (lower back), 22 and Heussler et al 23 were excluded because they had no placebo group. Studies by de Bie et al, 24 Ekim et al, 25 Rogvi-Hansen et al, 26 Aigner et al, 27 Yurtkuran et al, 28 and Shen et al 16 were excluded because there was no description of irradiation on the joint area or irradiation was performed only on the acupuncture points. Two studies from Konstantinovic et al 29,30 were excluded because the primary cause of pain in the subjects was radiculopathy.…”
Section: Excluded Studiesmentioning
confidence: 99%